Walt Disney's Cinderella Atelier Philippie Harchy ; story adaptation by Robyn Bryant. - Atelier Philippe Harchy; Bryant, Robyn; Walt Disney Company (Montreal, Quebec Brimar Pub., 1993)
With the help of her fairy godmother, a kitchen maid mistreated by her stepmother and stepsisters attends the palace ball where she meets the prince of her dreams.
Keywords: Fairy tales; Folklore -- France